Effect of low-cost white reflecting sling application on efficacy of phototherapy in healthy term neonates with non-hemolytic jaundice: A randomized controlled trial - Devpura, Kusum; Swami, Ghanshyam; Debbarma, Ripan; Udawat, Priyanka; Jangid, Amit (Indian Journal of Child Health, 2017)
Objective: The objective of this study was to evaluate the efficacy of white reflecting material (slings) hung from the sides of compact fluorescent lamp (CFL) phototherapy equipment in reducing the duration of phototherapy in healthy term neonates with non-hemolytic jaundice. Design: Randomized controlled trial. Setting: Postnatal ward of a tertiary level neonatal unit. Participants and Intervention: Healthy term neonates with non-hemolytic jaundice between 24 h and 14 days of age were randomly assigned to receive single surface phototherapy with (n=50) or without slings (n=50). Outcome Measure: Primary outcome was rate of reduction of serum bilirubin levels and secondary outcome was duration of phototherapy (hour) required. Results: Birth weight (2780±360 vs. 2790±260 g), gestation (38.22±1.0 vs. 38.08±0.90 week), and initial serum total bilirubin (17.36±1.06 vs. 16.96±1.20 mg/dL) were comparable between the two groups. There was a significant difference in the duration of phototherapy (mean ± standard deviation [SD]) between the sling (53.28±21.02 h) and no sling (62.88±20.22 h) groups (p=0.02). The irradiance of phototherapy equipment (?W/cm2/nm, mean±SD) was higher in sling group compared to no sling group (24.17±0.13 vs. 22.11±0.21). Conclusion: Hanging of white reflective sling on sides of CFL phototherapy equipment resulted in marginal increase in irradiance and reduction in the duration of phototherapy.